Magnetic Cobalt and Cobalt Oxide Nanoparticles in Hyperbranched Polyester Polyol Matrix - O. I. Medvedeva; S. S. Kambulova; O. V. Bondar; A. R. Gataulina; N. A. Ulakhovich; A. V. Gerasimov; V. G. Evtugyn; I. F. Gilmutdinov; M. P. Kutyreva (Journal of Nanotechnology)
A series of cobalt (Co) and its oxides based nanoparticles were synthesized by using hyperbranched polyester polyol Boltorn H20 as a platform and sodium borohydride as a reducing agent. UV, FT-IR, XRD, NTA, and TEM methods were employed to obtain physicochemical characteristics of the products. The average diameter of Co nanoparticles was approximately 8.2±3.4 nm. Their magnetic properties, including hysteresis loop, field-cooled, and zero field-cooled curves were investigated. The nanoparticles exhibit superparamagnetism at room temperature, accompanied by magnetic hysteresis below the blocking temperature.